Mental Health During the First Year of the COVID-19 Pandemic: A Review and Recommendations for Moving Forward. (July 2022) - Aknin, Lara B.; De Neve, Jan-Emmanuel; Dunn, Elizabeth W.; Fancourt, Daisy E.; Goldberg, Elkhonon; Helliwell, John F.; Jones, Sarah P.; Karam, Elie; Layard, Richard; Lyubomirsky, Sonja; Rzepa, Andrew; Saxena, Shekhar; et al.
COVID-19 has infected millions of people and upended the lives of most humans on the planet. Researchers from across the psychological sciences have sought to document and investigate the impact of COVID-19 in myriad ways, causing an explosion of research that is broad in scope, varied in methods, and challenging to consolidate. Because policy and practice aimed at helping people live healthier and happier lives requires insight from robust patterns of evidence, this article provides a rapid and thorough summary of high-quality studies available through early 2021 examining the mental-health consequences of living through the COVID-19 pandemic. Our review of the evidence indicates that anxiety, depression, and distress increased in the early months of the pandemic. Meanwhile, suicide rates, life satisfaction, and loneliness remained largely stable throughout the first year of the pandemic. In response to these insights, we present seven recommendations (one urgent, two short-term, and four ongoing) to support mental health during the pandemic and beyond.